Valoración de los recursos del ocio físico-deportivo : análisis y selección de atributos - Eva Sanz Arazuri; Ana Ponce de León Elizondo (Universidad de La Rioja, 2013)
This investigation tries, on one hand, to introduce the degree of satisfaction of real users to the offer of physical free time activities in the community of the University of La Rioja and on de other hand, to confirm which attributes aforementioned sport facilities, resources and activities are associated to the mentioned satisfaction. From this study it is detected that human and organizing factors are the attributes that most determine the real user satisfaction.